Strain rate dependence of a crash resistant adhesive as a function of temperature for the automotive industry. (November 2019) - Machado, JJM; Hayashi, A; Nunes, PDP; Marques, EAS; Carbas, RJC; Sato, C; da Silva, LFM
The wide and diverse application of adhesives in the automotive industry has increased over the last decades, driven by the need to produce efficient yet strong vehicles, able to meet both fuel economy and safety standards. This method allows to bond a variety of dissimilar materials used for structural parts, as well as to achieve lighter structures, and higher failure loads over other traditional methods such as fastening or welding. It is therefore important to understand the behaviour of adhesives under a wide range of strain rates and temperatures. These data are fundamental to ensure vehicle safety, as adhesives must be able to sustain impact conditions, deforming but at the same time keeping the integrity of the structure and transmitting the loads without damaging the joint. The aim and novelty of this work is the complete mechanical characterization of a high-performance crash resistant adhesive under varied strain rate and temperature conditions, necessary for the validation of structures used in the automotive industry. The mechanical behaviour of these materials is still poorly understood and described in the literature. The results showed a change in the mechanical properties of the adhesive with the variation of strain rate (quasi-static and impact of 3 m/s) and temperature (−30, 24 and 80 ℃). With the mechanical properties determined it was possible to define cohesive laws for implementation in finite element simulation, as a function of strain rate and temperature.